An Ordinance Regulating the Carrying of Loaded Firearms and Other Dangerous Weapons in the City of Troy, § 1, in Municipal Ordinances of the City of Troy (1905). - (:unkn) unknown (General Publisher, 1905)
Any person, other than a peace officer, who shall in any public street, highway or place within the City of Troy, have or carry concealed upon his person any loaded pistol, revolver, or other firearm, or any slungshot, billy, sand-club, or a dagger, dirk, stilletto, or dangerous knife, without theretofore having been authorized as hereinafter provided to carry the same, shall be guilty of a misdemeanor, punishable by a fine not exceeding one hundred and fifty dollars or by imprisonment in a penitentiary or county jail for not more than one hundred and fifty days, or by both.
--
Keywords: CARRY - CONCEALED